Stereotactic brainstem biopsy in a patient with coagulopathy of unclear etiology: case report - Beynon, Christopher; Wick, Wolfgang; Unterberg, Andreas; Kiening, Karl (Minimally invasive neurosurgery, 2012)
Parenchymal hemorrhage is one of the most feared risks of stereotactic brain biopsies potentially resulting in neurological deficits or even a fatal outcome. Patients with disorders of the coagulation system are at particular risk, so identifying these is one of the main tasks prior to surgery. Some patients may have a bleeding tendency despite normal laboratory values of the hemostatic system. We report the case of a patient with coagulopathy of unclear etiology undergoing a stereotactic brainstem biopsy. A medication scheme with tranexamic acid and desmopressin effectively decreased the patient’s bleeding time in vivo and the procedure was carried out without complications.